The perfect wife ebook A novel. - Delaney, JP (2019)
The perfect life. The perfect love. The perfect lie. From the bestselling author of The Girl Before comes a gripping psychological thriller. . . . “Mind-bending . . . Delaney takes domestic suspense beyond its comfort zone.”— The New York Times Book Review NAMED ONE OF THE BEST BOOKS OF THE YEAR BY THE NEW YORK PUBLIC LIBRARY • A COSMOPOLITAN NEW MUST-READ Abbie awakens in a daze with no memory of who she is or how she landed in this unsettling condition. The man by her side claims to be her husband. He’s a titan of the tech world, the founder of one of Silicon Valley’s most innovative start-ups. He tells Abbie that she is a gifted artist, an avid surfer, a loving mother to their young son, and the perfect wife. He says she had a terrible accident five years ago and that, through a huge technological breakthrough, she has been brought back from the abyss. She is a miracle of science.  But as Abbie pieces together memories of her marriage, she begins to question her husband’s motives—and his version of events. Can she trust him when he says he wants them to be together forever? And what really happened to her, half a decade ago? Beware the man who calls you . . .   THE PERFECT WIFE